Transfer of the anterior gluteus maximus to address abductor deficiency following soft tissue tumour excision. (5th February 2020) - Shea, Graham Ka-Hon; Ching-Hin Yau, Raymond; Wai-Hung Shek, Tony; Ho, Wai-Yip; Ying-Lee Lam, Albert
Hip abductor deficiency is most commonly encountered in the context of degeneration of the hip, and techniques for reconstruction pioneered by arthroplasty surgeons. We adopted a local muscle transfer technique utilizing the anterior half of the gluteus maximus for abductor reconstruction following soft tissue tumour excision in a young female patient. The patient of concern had a solitary fibrous tumour located between the right gluteus medius and minimus detected as an incidental finding. Marginal excision of the mass resulted in removal of the gluteus medius. The anterior half of the gluteus maximus was transferred and attached to the decorticated lateral greater trochanter by means of suture anchors and transosseous sutures. The patient initially demonstrated a Trendelenburg gait and limited abduction against gravity. By 1-year post-operation, there was return of normal gait and recovery of hip abductor power. This is the first report of anterior gluteus maximus transfer being successfully applied for soft tissue reconstruction around the hip subsequent to tumour excision.